Book review: Jerzy Witold Wiśniewski, Microeconometrics in Business Management, John Wiley & Sons, United Kingdom 2016 - Appenzeller, Dorota (Economics and Business Review, 2016)
Mathematical tools, especially econometric models, play an important, but still underestimated role in business management. The process of decision-making in a company requires increasing access to data. To make a proper decision the data must be analyzed in order to find regularities in the functioning of the economic entity. These regularities constitute the basis for the construction of tools for making forecasts or simulations and then decisions. It is econometrics which creates such tools. Generally two branches of econometrics can be distinguished: the theory of econometrics, which provides models and develops methods for their construction and applied econometrics, where theoretical  models are used for specific applications in a given economy or enterprise.